2015
DOI: 10.1177/0394632015617064
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25+Foxp3+ T regulatory cells, Th1 (CCR5, IL-2, IFN-γ) and Th2 (CCR4, IL-4, Il-13) type chemokine receptors and intracellular cytokines in children with common variable immunodeficiency

Abstract: Common variable immunodeficiency (CVID) is a heterogeneous group of primary antibody deficiencies characterized by decreased serum immunoglobulin G along with a decrease in serum IgA and/or IgM, defective specific antibody production, and recurrent bacterial infections. Abnormal lymphocyte trafficking, dysregulated cellular responses to chemokines, and uncontrolled T cell polarization may be involved in the pathogenesis and may help to understand the clinical complications. We evaluated T helper cell subsets (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 33 publications
1
31
0
3
Order By: Relevance
“…In contrast, Kutukculer et al [14] recently suggested that Treg cells do not play an important role in the pathogenesis of CVID. The authors reported percentages and absolute counts of Treg cells, with no significant difference between CVID patients and healthy controls or between patients with severe disease and patients with moderate disease [14].…”
Section: Regulatory T-cell Defectsmentioning
confidence: 92%
See 4 more Smart Citations
“…In contrast, Kutukculer et al [14] recently suggested that Treg cells do not play an important role in the pathogenesis of CVID. The authors reported percentages and absolute counts of Treg cells, with no significant difference between CVID patients and healthy controls or between patients with severe disease and patients with moderate disease [14].…”
Section: Regulatory T-cell Defectsmentioning
confidence: 92%
“…T H 1 cells seem to be more involved in pathogenesis than T H 2 cells. CVID patients with hepatomegaly had higher IL-2 and IFN-γ levels in stimulated CD4 + T cells, and patients with granuloma were found to have higher CCR5 expression in CD4 + T cells, suggesting that T H 1 cells may play a role in granuloma formation in CVID patients [14]. Overall, increased production of some chemokines [56] and cytokines, including IFN-γ [57], TNF-α [12], IL-12 [57], IL-9 [49], IL-4, and IL-10 [58] by T H subsets has been reported in CVID patients [59].…”
Section: Helper T-cell Defectsmentioning
confidence: 96%
See 3 more Smart Citations